Modified Milch Technique : A Safe and Painless Method for Reduction of Anterior Shoulder Dislocation. - Chaitanya, PR; PR, Chethan; PR, Naveen; M P, M P; Azeem, Abdul (International Journal of Medical Research and Review, 2014)
Background: The shoulder is the most commonly dislocated major joint in the body and this dislocation causes severe and agonizing pain. Prompt and painless reduction forms the cornerstone of treatment. We studied the efficacy of the Milch technique in the reduction of anterior dislocation of shoulder. Materials: Between September 2011 and March 2014, 60 cases of anterior dislocation of shoulder were reduced by Milch technique in C.S Hospital Shivamogga and Dhruva Orthopaedic Clinic Shivamogga and the pain experienced by the patient was quantified by Visual Analogue Score. Results: Reduction was successful in 56 cases (93.3%). The mean Visual Analogue score was 1.82. There were no complications. Conclusion: We conclude that the Milch technique is a very effective and relatively painless method for reducing anterior dislocation of the shoulder.